Algerian professional soccer specific aerobic endurance during competitive period - Abdelaziz, D. (Journal of Physical Education and Sport, 2011)
The aim of the current study was to assess the cardio-respiratory profile (VO2 max) of Algerian soccer players during competitive season, and secondly, to assess the effects of a close season training plan on end- season levels of fitness. Materials and Methods: seventeen soccer players were tested at (03) Three different time points throughout the competitive soccer season participated in the study, of which 17 second division forwards with an average age of 22.86 ± 2.56 years; height 180, 82 ± 3.68 cm; weight 80,20 ± 3,17 kg; body mass index 24,52± 0,40 kg/m2. To evaluate the VO2 max of players, the 20-m Multi Stage Shuttle Run Test (MST) protocol was used as recommended by (Leger et al., 1988). Results: of the total sample (n=17) with a general (range 45.00~66.85 ml/kg/min). A statistically significant differences between the VO2 max was assessed by MST method at the mid-season was significantly lower at the start of season period and at the end-season (51.49±4.77 vs. 54.43±5.38, 57.21±5.83 respectively; p<0.05; values are mean ± SD) as shown in the summary. Conclusion: Show that the Algerian second division football players tested have a normal VO2 max at the beginning of the preseason in comparison with the findings of other studies of international soccer players. It is possible to increase the performance of professional soccer players after the competitive period of 15 weeks duration.